PEMANFAATAN DAN KONSERVASI SUMBER AIR DALAM KEADAAN DARURAT - Adi, Seno (Jurnal Air Indonesia, 2009)
The need of clean water availability is the basic need of human being for living. In case of emergency, the clean water availability is still needed firstly. In this situation, we have to has a practical knowledge on water resource exploration as well as exploitation effectively and efficiently in such away the water utilization are sustainable. The water availability properties such as, quality, quantity, and site are related to the technology for water conservation and exploitation. Basically, the water availability in emergency could be developed based on the hydrological and hydro geological properties of the nearest location. In situ direct water utilization with bad water quality (in case of flooding) could be handled by using tools of water survival kit such as water bag, purification tablet or powder, and purification bottle. The water utilization in short term with limited scale (in case of refugees camp) could be developed by constructing shallow well (dig well or pumping well) if the shallow aquifer are available. The water utilization in medium term could be developed by constructing water conservation and exploitation system such as mini dam, infiltration galleries, spring water conservation, water seepage, and rain water harvesting. Key words : sumber air, darurat, hidrologi, hidrogeologi, konservasi